Aberrant expression of miR-138 as a novel diagnostic biomarker in systemic sclerosis. Issue 17 (December 2022) - Bayati, Paria; Poormoghim, Hadi; Mojtabavi, Nazanin
Background: MicroRNAs are short nucleotide sequences that contribute to the regulation of various biological functions and therefore their roles have been investigated in many pathologic conditions such as epithelial to mesenchymal transition in cancer and fibrosis; among them, miR-138 has been mostly studied in cancer biology and is well-known for its suppressing effect on cancer progression. Being able to suppress major pathways involved in EMT, miR-138 could be a good candidate to be investigated in fibrotic responses too. Based on our previous studies, and the capability of miR-138 to target and regulate several components of the EMT pathway; we hypothesized a role for miR-138 in systemic sclerosis. Accordingly, the gene expression of miR-138 was assessed to find any alterations in the whole blood of the SSc patients. Methods: Blood was collected from 70 patients with systemic sclerosis (equally divided between 2 groups of limited and diffuse categories) and 30 healthy individuals as controls. RNA was immediately isolated from the fresh whole blood; afterward, the resulting RNA was reverse transcribed into cDNA and then the relative expression of miR-138 was compared between the patients and the controls by the means of qPCR, and specific TaqMan primer and probes. Results: The relative expression of miR-138 was significantly lower in patients with systemic sclerosis compared to the controls. No significant difference was observed between the limited and diffuse patient groups. ROC curve analysis showed an appropriate diagnostic value of miR-138 in effectively differentiating SSc patients from the healthy controls. Conclusion: miR-138 is likely involved in the pathogenesis of SSc and with further evaluations may be utilized as a diagnostic biomarker in SSc. Also, targeting miR-138 in future studies could be promising for finding a novel treatment option for patients with SSc.